Effect of L-NAME on nitric oxide and gastrointestinal motility alterations in cirrhotic rats - Wang, Xin (World J Gastroenterol, 2002)
AIM: To investigate the effect of L-NAME on nitric oxide and gastrointestinal motility alterations in cirrhotic rats. METHODS: Rats with cirrhosis induced by carbon tetrachloride were randomly divided into two groups, one (n = 13) receiving 0.5 mg·kg(-1) per day of N G-nitro-L-arginine methyl ester (L-NAME), a nitric oxide synthase inhibitor, for 10 d, whereas the other group (n = 13) and control (n = 10) rats were administrated the same volume of 9 g•L⁻¹ saline. Half gastric emptying time and 2 h residual rate were measured by SPECT, using (99m)Tc-DTPA-labeled barium sulfate as test meal. Gastrointestinal transition time was recorded simultaneously. Serum concentration of nitric oxide (NO) was determined by the kinetic cadmium reduction and colorimetric methods. Immunohistochemical SABC method was used to observe the expression and distribution of three types of nitric oxide synthase (NOS) isoforms in the rat gastrointestinal tract. Western blot was used to detect expression of gastrointestinal NOS isoforms. RESULTS: Half gastric emptying time and trans-gastrointestinal time were significantly prolonged (124.0 ± 26.4 min; 33.7 ± 8.9 min; 72.1 ± 15.3 min; P < 0.01), (12.4 ± 0.5 h; 9.5 ± 0.3 h; 8.2 ± 0.8 h; P < 0.01), 2 h residual rate was raised in cirrhotic rats than in controls and cirrhotic rats treated with L-NAME (54.9% ± 7.6%, 13.7% ± 3.2%, 34.9% ± 10.3%, P < 0.01). Serum concentration of NO was significantly increased in cirrhotic rats than in the other groups (8.20 ± 2.48) μmol•L⁻¹, (5.94 ± 1.07) μmol•L⁻¹, and control (5.66 ± 1.60) μmol•L⁻¹, P < 0.01. NOS staining intensities which were mainly located in the gastrointestinal tissues were markedly lower in cirrhotic rats than in the controls and cirrhotic rats after treated with L-NAME. CONCLUSION: Gastrointestinal motility was remarkably inhibited in cirrhotic rats, which could be alleviated by L-NAME.Nitric oxide may play an important role in the inhibition of gastrointestinal motility in cirrhotic rats.